The growth performance of Rhizophora apiculata using the cut-propagule method for mangrove rehabilitation in Indonesia - ANDI HURUL AUNI USMAN; ADISTI PERMATASARI PUTRI HARTOYO; CECEP KUSMANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Usman AHA, Hartoyo APP, Kusmana C. 2022. The growth performance of Rhizophora apiculata using the cut-propagule method for mangrove rehabilitation in Indonesia. Biodiversitas 23: 6366-6378. A high decrease in the size of Indonesia's mangrove forests requires effective and efficient rehabilitation efforts. One of the efforts is using Rhizophora apiculata as the adaptive and fast-growing mangrove species and its cut-propagule seedling method for accelerating plant propagation. The objectives of this study were to analyze the growth performance of R. apiculata propagules with various treatments of propagule cutting, seedling media, and giving growth regulators (PGR), as well as to determine the best combination of treatment for the growth of R. apiculata. An experimental study was conducted in a greenhouse using a randomized design with 3 factors (propagule cutting, seedling media, and giving PGR) and 3 replications. The interaction of the combination of cut-propagule treatment, planting media, and growth regulator (AxBxC) only had a significant effect on the increase in the number of leaves of R. apiculata. Complete propagules and the lower part of cutting propagules with a combination of mud+sand seedling media and 10,000 ppm PGR (a0b1c1 and a2b1c1) resulted in the best value on the growth of R. apiculata. The cut-propagule seedling method of R. apiculata still showed good growth so it can be used as an alternative to mass vegetative reproduction in mangrove rehabilitation activity.